2015
DOI: 10.1103/physrevlett.115.115501
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo Calculation of the Binding Energy of Bilayer Graphene

Abstract: We report diffusion quantum Monte Carlo calculations of the interlayer binding energy of bilayer graphene. We find the binding energies of the AA-and AB-stacked structures at the equilibrium separation to be 11.5(9) and 17.7(9) meV/atom, respectively. The out-of-plane zone-center optical phonon frequency predicted by our binding-energy curve is consistent with available experimental results. As well as assisting the modeling of interactions between graphene layers, our results will facilitate the development o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
151
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(171 citation statements)
references
References 72 publications
(60 reference statements)
18
151
1
1
Order By: Relevance
“…On the other hand, since the walls are rotated, the well-known Bernal AB stacking is also observed, giving rise to the lowest interaction energy. These results are in agreement with ab initio calculations showing that ABstacked bilayer graphene is the most stable structure 35,36 . Considering now the case of unexpected (19,1)@ (19,14) DWNT (∆θ = 22.46…”
Section: Atomic Scale Simulationssupporting
confidence: 81%
“…On the other hand, since the walls are rotated, the well-known Bernal AB stacking is also observed, giving rise to the lowest interaction energy. These results are in agreement with ab initio calculations showing that ABstacked bilayer graphene is the most stable structure 35,36 . Considering now the case of unexpected (19,1)@ (19,14) DWNT (∆θ = 22.46…”
Section: Atomic Scale Simulationssupporting
confidence: 81%
“…3 Their results are obtained by means of infrared spectroscopy and X-ray analysis under high pressure. The P2 1 /c phase is stable up to pressures [20][21][22][23][24][25] GPa. This phase diagram only consists of two phases (I and II), and this same result has been reported by other experiments.…”
Section: Introductionmentioning
confidence: 91%
“…16 Quantum Monte Carlo (QMC), which approximately solves the electronic Schrödinger equation stochastically, 17 can yield highly accurate energies for atoms, 18,19 molecules, [20][21][22] and crystals. [23][24][25] Previous studies have shown that diffusion quantum Monte Carlo (DMC) can provide accurate energies for noncovalent interactions systems. [26][27][28][29][30] DMC can also produce an accurate description of the phase diagram of materials under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentation is much more difficult to conduct for bilayer graphene. Electronic-structure calculations yield dispersed values that may depend strongly on the particular AB, AA, or Moiré stacking [28]. To circumvent the problem, we have used a relationship demonstrated in the Appendix within the Girifalco model [29]:…”
Section: Graphene Foldingmentioning
confidence: 99%